Kariery naukowe kobiet w perspektywie systemowej - Wyleżałek, Joanna (Adult Education Discourses, 2020)
The XX and XXI social sciences discourse on social roles of women significantly inspired some change in female access to achieving socially valued goals. Despite being more and more dynamic that change did not result in a level playing field for women to develop professionally. This fact can be illustrated through diversified academic careers of women and men. Statistics (GUS 2019) show that more women receive higher education and postgraduate degrees. However, in terms of a further career, like post-doctoral degrees and professorship, there are significant disproportions between men and women. Women less often than men occupy important university positions or have their salaries grow in the same way. The author assumes that diversified dynamics of academic and professional promotions of men and women in the higher education system emerges from the specific strategies that are selected by the organisational actors. This issue is presented in the paper from the systemic point of view as well as the organisational games perspective or in other words the theory of the strategic actor by the French scholars Michel Crozier and Erhard Friedberg.